Pengembangan Media Pembelajaran Berbantuan Educaplay pada Materi Teks Negosiasi di Kelas X Sekolah Menengah atas Negeri 21 Medan. - Desi Alia Tumanggor; Ali Ali; Amaluddin Amaluddin (Medan Resource Center, 2026)
This study aimed to develop and evaluate the feasibility of Educaplay-assisted learning media for teaching negotiation texts in class X of SMA Negeri 21 Medan. The research applied a Research and Development (R&D) design using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study involved a population of 279 students, with a sample of 32 students from class X-1, as well as assessments from media and subject matter experts. Data were gathered through questionnaires and interviews. The findings revealed that the Educaplay-based learning media was categorized as highly feasible. Media experts provided an average score of 91.5%, which was classified as “very valid,” while subject matter experts gave an average score of 81.8%, also “very valid.” Additionally, the teacher’s evaluation produced a feasibility score of 96%, and students’ responses yielded an average score of 92.1%, indicating strong acceptance. Based on these results, it can be concluded that Educaplay-assisted learning media is both valid and feasible to enhance the learning process of negotiation text material in senior high school.